2021
DOI: 10.1021/acsomega.1c00166
|View full text |Cite
|
Sign up to set email alerts
|

Preanalytical Issues and Cycle Threshold Values in SARS-CoV-2 Real-Time RT-PCR Testing: Should Test Results Include These?

Abstract: Since the emergence of SARS-CoV-2 pandemic, clinical laboratories worldwide are overwhelmed with SARS-CoV-2 testing using the current gold standard: real-time reverse-transcription polymerase chain reaction (RT-PCR) assays. The large numbers of suspected cases led to shortages in numerous reagents such as specimen transport and RNA extraction buffers. We try to provide some answers on how strongly preanalytical issues affect RT-PCR results by reviewing the utility of different transport buffer media and virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 58 publications
0
67
0
Order By: Relevance
“…Payne et al wrote that over 60% of errors occur in the pre-analytical phase of any diagnostic process [ 43 ]. In the SARS-CoV-2 context, this phase includes the type of sample, the method of specimen collection, transport medium composition, storage conditions and time from sample collection to the RNA isolation [ 43 , 44 ]. The RNA extraction method and the RT-qPCR assay has also significant impact on Ct values, as demonstrated by this study [ 39 , 40 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Payne et al wrote that over 60% of errors occur in the pre-analytical phase of any diagnostic process [ 43 ]. In the SARS-CoV-2 context, this phase includes the type of sample, the method of specimen collection, transport medium composition, storage conditions and time from sample collection to the RNA isolation [ 43 , 44 ]. The RNA extraction method and the RT-qPCR assay has also significant impact on Ct values, as demonstrated by this study [ 39 , 40 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Ct value of a more sensitive kit represents a lower viral load compared to the same Ct of a less sensitive kit which needs thousands of more virus copies to reach the same Ct. Additionally, as discussed above, the identical Ct detected by the same assay has distinct infectivity potential if an early or late phase is detected. Without clinical data, the RT-PCR test cannot tell the disease phase [ 44 ]. Discrepancies between Ct values from different assays could be solved by normalisation by standard curve allowing Ct translation into copies/mL [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cutoff value of 34 cycles using an assay targeting the RdRp gene has been suggested for SARS-CoV-2 infectivity. 10 However, Ct values may well vary across sampling conditions and utilized assays. Furthermore, almost all positive samples fell within the highly transmissible B.1.1.7 lineage.…”
Section: Discussionmentioning
confidence: 99%
“…A serious concern in COVID-19 detection is the transportation of samples, and therefore pre-analytical parameters need to be optimized in each laboratory. To follow the protocol, clinical laboratories in the United State need to perform ‘bridging studies’ on FDA-approved 2019-nCoV diagnostic kits [ 116 ]. In this scenario, the effect of different sample types stored in variable transport/collection media on the performance of SARS-CoV-2 RT-PCR kits was evaluated [ 117 ] and concluded that transport media, 0.9% NaCl or amies media are compatible for nasopharyngeal, E-Swab or 3D-printed swabs.…”
Section: Optimization Of Covid-19 Detection Methods For Children and Older Adultsmentioning
confidence: 99%